THE INFLUENCE OF CONFLICTS ON TOURISM DEVELOPMENT: METHODOLOGY OF SOCIO-GEOGRAPHICAL STUDY - ZAVARIKA, Galina (Ekonomichna ta Sotsialna Geografiya, 2018)
The paper focuses on the methodological issues of socio-geographical research of conflicts in reference to their influence on the tourism development. The relevance of the investigated question is obvious given great reduction of tourism development indicators in Ukraine due to the conf lict in the eastern par t of the country and touchy situation in the country in general. However, few methodological researches have dealt with the social conflicts and their influence on tourism. Objective complexity of the research is connected with the fact that the given research subject has interdisciplinary nature and, therefore, implies the use of wide array of methods. Thus, the author proposes, lies out and discusses cer tain general and special scientif ic methods in reference to the inf luence of the social conflicts on the tourism development. Since the substantiation of socio-geographical approach to the study of conf lict impact on tourism was the main objective of the paper, the proposed methods are described in accordance with the scope and subject of socio-geographical research with specific examples of their possible use additionally provided. The proposed approach includes six interrelated stages of research: 1. identification of phases and directions of influence of socio-political conf lict on tourism development; 2. assessment of tourism development dynamics, including main trends, in instability conditions; 3. detection of shifts in the structure of tourism; 4. identif ication of directions of tourism transformation as a result of the conflict; 5. forecasting the opportunities for tourism development in the post-conflict period; 6. providing recommendations for the solution of the socio-geographical problems for tourism development under the conditions of instability and during the stabilization period. The relevant research methods are proposed for the each stage of research. The proposed approach was tested by the author on Luhansk and Donetsk regions of Ukraine as territories affected by the conflict.

Стаття присвячена методичним питання суспільно-географічного дослідження конфлікту. Виявлено загальнонаукові методи, які запропоновано використовувати при дослідженні впливу конфліктів на розвиток туризму. Встановлено актуальність досліджуваного питання, яка полягає в сучасному суттєвому зниженні темпів розвитку туризму внаслідок конфлікту не тільки в східному регіоні, а і цілком в країні. З’ясовано, що методологічні засади дослідження конфліктів слабо розроблені в сучасній географії. Охарактеризовано запропоновані методи у відповідності до об’єкту та предмету суспільно-географічного дослідження та наведені конкретні приклади їх можливого використання. Вперше розроблено методику суспільно-географічного дослідження впливу конфлікту на туризм, що і є метою даної роботи. Ця методика апробована на прикладі Луганської та Донецької областей як регіонів, постраждалих внаслідок конфлікту. Вона містить шість взаємопов’язаних етапів робіт, а саме: виявлення етапів і напрямів впливу конфлікту на розвиток туризму; оцінка тенденцій динаміки розвитку туризму в умовах нестабільності; виявлення зрушень в структурі туризму; визначення напрямів трансформації туризму внаслідок конфлікту; прогнозування можливостей розвитку туризму в постконфліктний період; розробка рекомендацій по вирішенню суспільно-географічних проблем розвитку туризму в умовах нестабільності та в період стабілізації.
МЕТОДИКА СУСПІЛЬНО-ГЕОГРАФІЧНОГО ДОСЛІДЖЕННЯ ВПЛИВУ КОНФЛІКТІВ НА РОЗВИТОК ТУРИЗМУ
Keywords: tourism; conflict; methodology; principle; methods; interdisciplinarity; туризм; конфлікт; методологія; принцип; методи; міждисциплінарність